Integration host factor of Escherichia coli reverses the inhibition of R6K plasmid replication by pi initiator protein. - Dellis, S (1991)
Integration host factor (IHF) protein is the only host-encoded protein known to bind and to affect replication of the gamma origin of Escherichia coli plasmid R6K. We examined the ability of R6K origins to replicate in cells lacking either of the two subunits of IHF. As shown previously, the gamma origin cannot replicate in IHF-deficient cells. However, this inability to replicate was relieved under the following conditions: underproduction of the wild-type pi replication protein of R6K or production of normal levels of mutant pi proteins which exhibit relaxed replication control. The copy number of plasmids containing the primary R6K origins (alpha and beta) is substantially reduced in IHF-deficient bacteria. Furthermore, replication of these plasmids is completely inhibited if the IHF-deficient strains contain a helper plasmid producing additional wild-type pi protein. IHF protein has previously been shown to bind to two sites within the gamma origin. These sites flank a central repeat segment which binds pi protein. We propose a model in which IHF binding to its sites reduces the replication inhibitor activity of pi protein at all three R6K origins.